Longitudinal Circulating Tumor DNA Profiling in Metastatic Colorectal Cancer During Anti-EGFR Therapy - Yang, Wentao; Zou, Jianling; Li, Ye; Liu, Rujiao; Yan, Zhengqing; Chen, Shiqing; Zhao, Xiaoying; Guo, Weijian; Huang, Mingzhu; Li, Wenhua; Zhu, Xiaodong; Chen, Zhiyu (Frontiers in Oncology, 2022)
Abstract Background: Metastatic colorectal cancer (mCRC) is a heterogenous disease with limited precision medicine and targeted therapy options. Monoclonal antibodies against epidermal growth factor receptor (EGFR) have been a crucial treatment option for mCRC. However, proper biomarkers for predicting therapeutic response remain unknown. As a non-invasive test, circulating tumor DNA (ctDNA) is appropriately positioned to reveal tumor heterogeneity and evolution, as it can be used in real-time genomic profiling. To evaluate the significance of ctDNA in monitoring the dynamic therapeutic response and prognosis of mCRC, we detected the baseline and dynamic changes of ctDNA in mCRC patients receiving anti-EGFR therapies. Methods: A single-center study was conducted retrospectively. Plasma samples from mCRC patients who received anti-EGFR therapies were collected at baseline and continuous treatment points. The ctDNA was extracted and sequenced with a target panel of tumor-related genes via next-generation sequencing (NGS). Clinical information was also collected and analyzed. Results: We conducted dynamic sampling of 22 mCRC patients, analyzed 130 plasma samples, obtained a baseline genomic mutation profile of the patients. In total, 54 variations were detected in 22 plasma samples, with a positive rate of 77.3% (17/22). TP53 was the most mutated gene (59.1%, 13/22), followed by APC (18.2%, 4/22). There was a high concordance rate of genomic characteristics between the tumor tissue test by polymerase chain reaction and ctDNA test by NGS. The mutation discrepancy increased with an extended course of treatment. During remission TP53 and APC were the most frequently decreased clonal mutations and KRAS, NRAS, ERBB2 and PIK3CA were the most decreased subclonal mutations. Both mutation types were increased during progression. The ctDNA decreased earlier than did the responses of computed tomography and traditional tumor markers (carbohydrate antigen 19-9 and carcinoembryonic antigen [CEA]). Lactate dehydrogenase level (P = 0.041), CEA level (P = 0.038), and primary lesion site (P = 0.038) were independent risk factors that influenced overall survival. Moreover, patients with RAS mutations tended to have a worse prognosis (P = 0.072). Conclusions: This study demonstrates that ctDNA is a promising biomarker for monitoring the dynamic response to treatment and determining the prognosis of mCRC.